Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
1x + 3y - 1z = 2 ⇒ 1x + 3y - 1z = 2
1x - 2y + 3z = 7 ⇒ 1x - 2y + 3z = 7
1x + 2y - 5z = -21 5y - 4z = -5
5y - 4z = -5 ⇒ -20y + 16z = 20
1x + 3y - 1z = 2 -4y + 8z = -28 ⇒ -20y - 40z = -140 1x - 2y + 3z = 7 ⇒ 1x - 2y + 3z = 7 -24z = -120
1x + 2y - 5z = -21 ⇒ 1x + 2y - 5z = -21 -24 -24
-4y + 8z = -28 z = 5
5y - 4(5) = -5
5y - 20 = -5
+20 +20
5y = 15
5 5
y = 3
x + 3(3) - 5 = 2
x + 9 - 5 = 2
x + 4 = 2
-4 -4
x = -2
(x, y, z) = (-2, 3, 5)
The solution to the answer is B. (-2, 3, 5).
1x - 2y + 3z = 7 ⇒ 1x - 2y + 3z = 7
1x + 2y - 5z = -21 5y - 4z = -5
5y - 4z = -5 ⇒ -20y + 16z = 20
1x + 3y - 1z = 2 -4y + 8z = -28 ⇒ -20y - 40z = -140 1x - 2y + 3z = 7 ⇒ 1x - 2y + 3z = 7 -24z = -120
1x + 2y - 5z = -21 ⇒ 1x + 2y - 5z = -21 -24 -24
-4y + 8z = -28 z = 5
5y - 4(5) = -5
5y - 20 = -5
+20 +20
5y = 15
5 5
y = 3
x + 3(3) - 5 = 2
x + 9 - 5 = 2
x + 4 = 2
-4 -4
x = -2
(x, y, z) = (-2, 3, 5)
The solution to the answer is B. (-2, 3, 5).
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.